REPRESENTASI PERILAKU BODY SHAMING PEREMPUAN DALAM FILM PENDEK DUNIA SEMPIT (Analisis Semiotika Roland Berthes) - Marissa Anggelina (2023)
Cases of violence against women are still a big problem that until now and still frequently occur throughout the world, especially in Indonesia. Violence against women can occur anywhere, both in public places, at work and even in the home. Violence that often occurs against women is very common, such as physical, psychological and sexual violence. Usually the violence that is always visible is sexual violence, but many also experience physical and psychological violence. Currently, psychological violence itself does not receive more attention from society, even though this violence actually makes victims feel very depressed. The psychic violence that is currently happening to women is body shaming, where body shaming is a comment on body shape that is not ideal. Body shaming behavior is a form of action to criticize and insult a person's physical form. Film is one representation in the real world. One of the films that raises the issue of body shaming is the Dunia Sempit short film. This study aims to discuss the representation of behavior in dealing with Body Shaming in the short film Dunia Sempit by using a semiotic analysis approach from Roland Barthes. The research method used is descriptive qualitative using primary data sources and secondary data. This research technique used data in the form of films so that the data collection technique was carried out by watching the entire Dunia Sempit short film to obtain an overview of the short film, then observing each scene contained in the Dunia Sempit short film, selecting the scenes that represent how the behavior in dealing with body shaming is to be analyzed in research, enter data in the form of scene cuts or screenshots showing the Representation of Behavior in the face of Body Shaming, and analyze or review the data using Roland Barthes' Semiotics. The final results of this study indicate that the body shaming behavior in the Dunia Sempit short film emphasizes that women get more body shaming behavior and the results in this study also find ways to deal with body shaming behavior that occurs against victims.